Lurking Infantile Pertussis: Experience from a Tertiary Care Center in Northern India - Bhattacharya, Deepanjan; Dash, Nabaneeta; Kavitha, Thondi Kkandy; Sharma, Megha; Gautam, Vikas; Verma, Sanjay (Journal of Pediatric Infectious Diseases, 2020)
Objectives The aim is to study the clinical laboratory profile and outcome of infants with laboratory confirmed pertussis.Methods In this retrospective study, records of 30 infants with laboratory confirmed pertussis, admitted to the pediatric department of a tertiary care hospital, were reviewed. Clinical features, laboratory parameters, and outcomes were noted.Results Median (interquartile range age was 10 (7–24.5) weeks, with a male preponderance. Large majority (60%) of enrolled infants were less than 16 weeks of age and nine (30%) developed pertussis even before 8 weeks of age. Cough was universal (100%), followed by rapid breathing (73%), fever (70%), and apnea (10%). Bubble continuous positive airway pressure (CPAP), nasal prongs oxygen, and invasive ventilation were required in 15 (54%), 11 (39%), and 2 (7%) infants, respectively; 12 (40%) needed to be admitted to the pediatric intensive care unit. Anemia was observed in 28 (93%) and leukemoid reaction in 15 (50%). All except one were discharged successfully. None of the mothers had received tetanus, diphtheria, and pertussis or Tdap vaccination during pregnancy.Conclusion Our study reports the continued occurrence of infantile pertussis in the community, suggesting reconsideration of our vaccination policy, including maternal immunization.
Keywords: pertussis; infancy; leukemoid reaction; India